منہاج القرآن اور دعوتِ اسلامی کی خدمات کا تجزیاتی مطالعہ - Asma Aziz; Saba Tariq (الآفاق اسلامی و تحقیقی مجلہ, 2022)
Minhaj-ul-Quran and Dawat-e-Islami is a global mission for the sace of Pakistan. The Islamic parties of Pakistan came into being with a very clear goal. Their goal was to spread Islam in the land of Allah and he was convinced and satisfied with the reality of this goal. Religious parties started when the fire of apostasy spread in the ignorant villages of Pakistan and Muslims who were ignorant of their religion and alienated from God and His Messenger were engulfed in this fire. To extinguish this fire, Muslims from all sides rose up and the preaching parties / Tablighi Jammat became enthusiastic. During this period, Dr. Muhammad Tahir ul Qadri, Syed Abu Ali Maududi, Hafiz Muhammad Saeed, Muhammad Ilyas Qadri tried to preach. And launched a universal movement for this purpose and performed the duty of reform and training for the propagation of Islam. And even today they are carrying out their duty of spreading Islam in the non-Muslim world. Minhaj-ul-Quran International and Da’wah-e-Islami are also such movements which have fulfilled their duty of reform, training and propagation of religion all over the world. Minhaj-ul-Quran International and Da’wah Islami are two such movements which are carrying out their duty of reform, training and propagation of religion all over the world. Under the title of the article, Minhaj-ul-Quran and the method of preaching of Da’wah Islami, comparative and research review, the method and services of preaching of Minhaj-ul-Quran and Da’wah Islami will be reviewed.